5-HT1B receptor agonists promote Schwann cell myelination - Yuka Kobayashi-Ujiie; Keiko Hiraki-Kamon; Shuji Wakatsuki; Toshiyuki Araki (PLoS ONE, 2026)
Congenital demyelinating peripheral neuropathy causes severe sensorimotor defects, affecting patient mobility. To identify therapeutic compounds for peripheral hypomyelinating neuropathy, we performed an unbiased screening of annotated compound library by in vitro myelination culture model using Trembler (Tr-Ncnp) -derived dorsal root ganglia explants. Among the compounds identified in the screening, we confirmed that zolmitriptan, a 5-hydroxytryptamine 1B/1D receptor agonist, promotes myelination in culture. Zolmitriptan up-regulated myelin-related genes in primary Schwann cells and increased proliferating Schwann cells along axons in DRG explant cultures of Tr-Ncnp mice. Furthermore, we observed that chronic administration of zolmitriptan ameliorates sensorimotor dysfunction in Tr-Ncnp mice. Collectively, these results suggest that 5-HT1B/1D receptor agonists may increase Schwann cells participating in myelination, and consequently ameliorate myelination impairment in peripheral neuropathy.